DEVELOPMENT OF MOBILE FIRE PROTECTION MEANS – ROLL FIRE PROTECTION MATERIALS. LITERATURE REVIEW - ТАРАН, Н. А.; ШОЛОГОН, В. І.; ВАХІТОВ, Р. А.; РАЄНКО, Г. Ф.; КАЛАФАТ, К. В.; БЕССАРАБОВ, В. І. (Technologies and Engineering, 2025)
Purpose. Determination of modern trends in the improvement of fire protection roll materials aimed at increasing their fire resistance, mechanical strength and environmental safety, to find innovative technical solutions for the development of mobile fire protection equipment. Methodology. The methods of literature-system and critical analysis, the method of summarising the results from different sources to create a holistic picture of the state of the scientific problem, the method of comparative analysis of different approaches used in research on the topic of the review were used. Findings. It is shown that one of the current trends in the development of the fire protection industry is the creation and organisation of mobile fire protection, which can be used for fire protection of ammunition storage sites in the field. The scientific papers and practical implementations of various types of fire protection roll materials - fire protection blankets, flexible products with intumescent coating or heat-resistant filling, etc. are considered. It is substantiated that reinforcement of fire retardant blankets is an important process that contributes to the improvement of mechanical properties and efficiency of the fire protection means. The existing methods of obtaining fibres and textile materials with reduced flammability used in the manufacture of fire protection roll materials are analysed. It is shown that an effective means that combines the best qualities of constructive and intumescent fire protection is the use of flexible swellable fire protection materials. The patent information, formulations and manufacturing technologies for mobile intumescent fire protection means are analysed. Originality. For the first time, on the basis of an array of literature data and patent search, the analysis and generalisation of literature data on the composition, technological aspects of manufacturing, characteristics of fire protection efficiency of flexible fire protection products as a component of mobile fire protection in the field to ensure long-term operation without loss of protective properties was carried out. Practical value. Practical recommendations on the composition, effect of innovative fire retardant additives and nanomaterials, and manufacturing technology of fire retardant roll materials that can be used for fire protection of defence, construction and industrial facilities have been provided.